Driving, a spiritual experience - Damour, Franck (Razón y fe, 2022)
On average, Europeans use their car six hours a week. It is much less than a smartphone or a TV, but it is enough to make it one of the most used technical objects. The car is not a neutral and transparent accessory, it changes our perception and access to the world. Driving is thus one of those technical practices on which our humanity is constituted. This means that developments in the automobile industry are not unrelated to our spiritual life.
Keywords: spirituality; technology; anthropology; automobility